(untitled) (Scientia Agropecuaria, 2023)
There are several investigations on the use of food waste to remove contaminants by adsorption. However, a simple route, without chemical activation reagents, is needed for the development of adsorbents. The aim of this study was to develop an adsorbent from plantain peel, using a simple procedure, and to evaluate its capacity to remove phosphate from aqueous solutions at phosphate concentrations similar to those of water sources at risk of eutrophication (0.30 mg/L). The simple pyrolysis method was used in an electric muffle, without chemical activation, using plantain peel as precursor. The variables evaluated were pyrolysis temperature and solution pH. The specific surface area BET, zero loading point of the developed treatments, was determined. Phosphate adsorption was studied in a batch experiment in the presence of calcium ions in solution. Phosphate adsorption was favorable at all three pyrolysis temperature levels (500, 600 and 700 °C) and two solution pH levels (pH 7 and 10). the pseudo-second order kinetic model was the best fit for the experimental data to describe the adsorption mechanism. The best fit to the experimental equilibrium data was obtained with the Langmuir isotherm model. It was found that a 1 g/L dose of the adsorbent was able to reduce 92% of phosphate in water, with a removal capacity 0.14 mg/g at pH 10 and pyrolysis temperature of 700 °C. This study lays the groundwork for future research on the use of this type of adsorbent in water treatment to facilitate access to clean water for rural populations.